2017
DOI: 10.1086/692570
|View full text |Cite
|
Sign up to set email alerts
|

The Breakdown of Static and Evolutionary Allometries during Climatic Upheaval

Abstract: 15The influence of within-species variation and covariation on evolutionary patterns is 16 well established for generational and macroevolutionary processes, most prominently 17 through genetic lines of least resistance. However, it is not known whether intraspecific 18 phenotypic variation also directs microevolutionary trajectories into the long term 19 when a species is subject to varying environmental conditions. Here we present a 20 continuous, high-resolution bivariate record of size and shape changes am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…This changed when Hunt (Hunt, , ; Hunt, Bell, & Travis, ; Hunt, Hopkins, & Lidgard, ; Hunt, Wicaksono, Brown, & Macleod, ) developed a model framework that allowed an objective evaluation of relative fit of different models to fossil time series based on their AIC scores. Hunt's models of the canonical modes stasis, directional change and random walk are widely used when analysing phyletic time series and his model framework has greatly advanced our ability to interpret the fossil record (e.g., Brombacher, Wilson, Bailey, & Ezard, ; Hopkins & Lidgard, ; Hunt, ; Hunt et al., ; Pearson & Ezard, ; Spanbauer, Fritz, & Baker, ; Voje, ).…”
Section: Introductionmentioning
confidence: 99%
“…This changed when Hunt (Hunt, , ; Hunt, Bell, & Travis, ; Hunt, Hopkins, & Lidgard, ; Hunt, Wicaksono, Brown, & Macleod, ) developed a model framework that allowed an objective evaluation of relative fit of different models to fossil time series based on their AIC scores. Hunt's models of the canonical modes stasis, directional change and random walk are widely used when analysing phyletic time series and his model framework has greatly advanced our ability to interpret the fossil record (e.g., Brombacher, Wilson, Bailey, & Ezard, ; Hopkins & Lidgard, ; Hunt, ; Hunt et al., ; Pearson & Ezard, ; Spanbauer, Fritz, & Baker, ; Voje, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the species level, the fine structure of phenotypic (co) variation seems to be fairly labile. It can change rapidly in response to directional selection, even in natural populations (e.g., Assis, Patton, Hubbe, & Marroig, 2016); the variation signal in fossil ostracods fades over a few million years (Hunt, 2007), with a similar timeframe reported by Schluter (1996) from estimated divergence times for extant taxa; it is disrupted in planktic foraminifera by climate shifts (Brombacher, Wilson, Bailey, & Ezard, 2017); and static allometry-that is intraspecific variation among adults-while stable within species generally does not seem to persist among related species (Voje, Hansen, Egset, Bolstad, & Pélabon, 2014). At higher levels within larger clades, the direction and eccentricity of larger-scale multivariate variation is stable -and predictive of evolutionary patterns-within ungulate families and bird clades but differs among them (Haber, 2016;Watanabe, 2018).…”
Section: Direction Biasmentioning
confidence: 94%
“…Thus, alternative mechanisms must also be considered, including release from interactions with pterosaurs, nonavian dinosaurs, and Mesozoic bird lineages outside the crown, all of which were lost at the end of the Mesozoic Era. For example, in Plio-Pleistocene planktic foraminifera, evolutionary changes tend to be aligned with allometric patterns, but shifts in climate state drive clades in different directions (Brombacher et al, 2017). An intermediate, intuitively appealing, possibility is that the loosening and later tightening of developmental bias occurs only at the origin of clades that are founded via an evolutionary novelty sensu G. P. Wagner (2014), that is a trait lacking homology in the ancestor, or radically and irreversibly altered from the ancestral state.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…In contrast to comparable cases where fossil material is used (e.g. Weinkauf et al 2014, Brombacher et al 2017), we are here in the unique situation that the extinction events can nearly exclusively be linked to salinity increase (Rohling et al 2009), allowing a qualification of the stressor which acted on the assemblage.…”
Section: Introductionmentioning
confidence: 95%
“…Understanding the morphological reaction of Foraminifera toward environmental stress could serve as a proxy for environmental reconstructions and further our understanding of evolvability of this organismal group. Past studies have shown that morphological deviations in benthic and planktonic Foraminifera can be caused by environmental forcing (Malmgren and Kennett 1976, Malmgren 1984, Baumfalk et al 1987, Mary and Knappertsbusch 2013, Moller et al 2013, Weinkauf et al 2014, Knappertsbusch 2016, Brombacher et al 2017. But since these studies quantified morphology in very different ways, the results obtained are scarce and controversial.…”
Section: Introductionmentioning
confidence: 99%